A new infraspecific arrangement of Teucrium thymifolium (Lamiaceae), an aggregate endemic to the Iberian Peninsula. (3rd September 2018) - Crespo, Manuel B.; Alonso, Mª Ángeles; Martínez Azorín, Mario
Abstract: In the framework of our studies on Lamiaceae from the eastern Iberian Peninsula, for the forthcoming fourth volume of Flora valentina, a new infraspecific arrangement is proposed here for the Iberian endemic Teucrium thymifolium . Besides the type subspecies, T. thymifolium subsp. thymifolium, which is widely distributed through the eastern Iberian Peninsula, two new nomenclatural combinations are established: (i) T. thymifolium subsp. fraternum (Pau) M.B. Crespo, M.A. Alonso & Mart.-Azorín (= T. terciae ), for the thermophilous populations growing in SE Murcia province, and (ii) T. thymifolium subsp. hervieri (Briq. & Debeaux) M.B. Crespo, M.A. Alonso & Mart.-Azorín, for Subbaetic inland populations from where the provinces of Albacete, Jaén and Granada come into contact. Nomenclatural types and data on distribution and ecology are reported for all accepted subspecies, including the designation of a lectotype for T. thymifolium subsp. hervieri . Furthermore, relationships of the latter to the recently described T. moleromesae Sánchez Gómez et al. are briefly discussed, both taxa being treated here in synonymy.